PENGGUNAAN EGG SHELL POWDER (ESP) DAN SUGARCANE PULP ASH (SPA) SEBAGAI BAHAN STABILISASI TERHADAP KUAT DUKUNG TANAH LEMPUNG - Fitridawati Soehardi; Marta Dinata (Racic : Rab Construction Research, 2023)
Repairs to clay soils generally use stabilization methods to improve the properties of clay soils with additional materials mixed in the original clay soil to increase the soil bearing strength according to technical specifications in building construction. Egg Shell Powder (ESP) is a waste product from households and home industries with a high enough calcium carbonate (CaCO3) content to fill the holes between the pores and glue the soil particles together. Meanwhile, Sugarcane Pulp Ash (SPA) is one of the wastes from household products and sugarcane processing that is not utilized by the surrounding community to reduce environmental pollution. The research method used in this study was laboratory testing of the water content, specific gravity, and CBR values ​​of the addition of ESP and SPA to clay with variations of 0%, 5%, 10%, and 15% and to the addition of 5% SPA. Results The original soil in this study was included in the CL soil classification, namely non-organic clay with low to moderate plasticity. The optimum water content value tends to decrease along with the addition of ESP and SPA to the original soil, namely the variation of ESP 15% and SPA, which is 19%, and the specific gravity value increases by 1,71 gg/cc. The CBR value increased with the addition of 15% ESP and 5% SPA, which was 9,23%.